Tips from the Experts on Conducting and Reviewing Qualitative Research. (1st June 2018) - DeVaney, Sharon A.; Spangler, Alice; Lee, Young‐A; Delgadillo, Lucy
Abstract : The purpose of this article was to describe the characteristics of qualitative studies, explain the various types of qualitative studies, and indicate which data collection method fits which type of qualitative study. Also, the authors who are all Associate Editors of the Family and Consumer Sciences Research Journal have provided their ideas on conducting reviews of qualitative studies. This article is an extension of the panel that was presented at the Annual Conference of the American Association of Family and Consumer Sciences in June 2018.